Adsorption and Recovery Studies of Cadmium and Lead Ions Using Biowaste Adsorbents from Aqueous Solution - Liang Feng; Enju Wang (Separations)
The use of low-cost biowaste adsorbents for the removal of toxic metal ions from aqueous solutions offers significant environmental benefits. This research evaluated the adsorption and recovery of Cd2+ and Pb2+ ions in batch and column modes with luffa peels and chamomile flowers. The biosorbents were treated with 0.4 M nitric acid or with 0.4 M NaOH base. An FTIR analysis of the sorbents indicated that surface OH, C=O, CO and COO groups played a role in the adsorption process. L-type isotherms were obtained for Pb2+, fitting both the Langmuir and Freundlich models, with maximum adsorption capacities of 34.0 mg/g for luffa peels and 49.5 mg/g for chamomile flowers. Adsorption isotherms for Cd2+ ion fit better with the Freundlich model with smaller adsorption capacity than Pb2+. Base-treated sorbents have higher adsorption capacity. The adsorption kinetic for both ions are fast and followed a pseudo-second order chemosorption model. Fixed-bed column dynamic adsorption with luffa peels obtained a Thomas dynamic adsorption capacity of 32.9 mg/g for Pb2+ and 25.8 mg/g for Cd2+. The recovery efficiency was 87 to 90% over three adsorption–regeneration cycles.